The Strategy of Utilizing Digital Technology to Enhance the Reach of Da’wah Among the Millennial Generation - Dini Fitriani, Ajeng (Sekolah Tinggi Agama Islam Kuningan, 2025)
The rapid advancement of digital technology has significantly transformed religious communication patterns, particularly Islamic da’wah among Indonesia’s millennial generation. Millennials, characterized by high digital literacy and preference for interactive, visual, and on-demand content, increasingly rely on social media platforms as primary sources of spiritual information. However, many da’wah initiatives still replicate conventional one-way preaching models without adapting to the dynamics of digital ecosystems. This study aims to identify effective strategies for utilizing digital technology to enhance the reach and impact of da’wah among millennials. Employing a qualitative case study design, data were collected through in-depth interviews with digital da’wah practitioners and millennial audiences, participant observation of online religious content, and documentation analysis. The findings reveal that authenticity, relatability, visual storytelling, and engagement-based communication significantly influence audience retention and participation. Instagram, YouTube, and TikTok emerged as the most effective platforms when content was tailored to platform-specific formats such as short-form videos, live streaming, and interactive features. The study concludes that successful digital da’wah requires a paradigm shift toward conversational, contextual, and multi-platform strategies while maintaining theological credibility. These findings contribute to the development of digital religion scholarship and provide practical guidance for Islamic communicators navigating the contemporary digital landscape.